Javelin Throw Training Model Bassed Medicine Ball - Widiyatno; Fikri, Aprizal; Satria, M. Haris (Universitas PGRI Palembang, 2025)
This study aims to develop and evaluate the effectiveness of a medicine ball-based javelin throwing training model on improving upper body strength, motion coordination, and throwing distance in athletic athletes in Palembang City. The research method used is an experimental method with a quantitative approach. The sample consisted of 30 javelin throwing athletes who were divided into two groups, namely the experimental group given a medicine ball-based training program and the control group that continued to undergo conventional training. The training is conducted for eight weeks with a frequency of three times a week. Data collection was carried out through practical tests of javelin throwing, measurement of arm and shoulder muscle strength using a dynamometer, and analysis of throwing techniques through video recording. The results showed that the experimental group experienced a significant increase in average throwing distance by 12.5%, an increase in muscle strength by 18%, and visual improvement in throwing technique. Based on these findings, it can be concluded that the medicine ball-based training model makes a positive contribution to improving the performance of javelin throwing athletes. Therefore, this model is recommended as an alternative to an innovative and effective training program in the development of athletic athletes.